1990
DOI: 10.1002/mrd.1080270209
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between follicular fluid steroid hormone concentrations, oocyte maturity, in vitro fertilization and embryonic development in the rhesus monkey

Abstract: Oocytes and matched samples of follicular fluid (FF) were obtained from 70 follicles of five rhesus monkeys stimulated with either pregnant mare serum gonadotropin or human menopausal gonadotropin. Follicular aspiration was performed 30-32 h after human chorionic gonadotropin administration. The concentrations of estradiol (E2), progesterone (P), testosterone (T), and dihydrotestosterone (DHT) in FF were measured. Twenty-six percent of oocytes were classified as mature (M), 41% matured in vitro (Miv), 13% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…Due to the lack of sufficient hormonal support of P 4 , oocyte maturation is arrested and the subsequent processes, including fertilization, blastocyst formation and embryo development, are negatively affected. This hypothesis is in accordance with previous experiments on rhesus monkeys, which reported that a higher ratio of P 4 to E 2 in the FF was beneficial for the development of the embryos (72). In addition, this is consistent with the findings of Gustafson et al (73), suggesting that a higher E 2 /P 4 ratio in the FF was associated with a lower IVF success rate.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the lack of sufficient hormonal support of P 4 , oocyte maturation is arrested and the subsequent processes, including fertilization, blastocyst formation and embryo development, are negatively affected. This hypothesis is in accordance with previous experiments on rhesus monkeys, which reported that a higher ratio of P 4 to E 2 in the FF was beneficial for the development of the embryos (72). In addition, this is consistent with the findings of Gustafson et al (73), suggesting that a higher E 2 /P 4 ratio in the FF was associated with a lower IVF success rate.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the culture environment needed to support the meiotic maturation of all oocytes may be inadequate. Previous studies [31,32] on primate oocyte maturation have been conducted without regard to menstrual cycle phase, presumably because of resource scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the high concentration of progesterone in follicular fluid induces meiotic maturation of rhesus monkey oocytes [22]. During in vitro maturation of COCs, progesterone was produced by cumulus cells, and the level of progesterone in the medium was increased by stimulation with FSH and/or LH in humans [23,24] and pigs [14,20].…”
Section: Discussionmentioning
confidence: 99%